Executive Committee Minutes 2014-10-02 - Academic Senate:::::::::
Agenda approved. Minutes of 9/18 approved. Chair Report. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President of Administration and Finance Report – C. Dinno for L. Furukawa-Schlereth. Vice President of Student Affairs Report. SSU SETE Policy approved for Senate agenda. Information Item: AS resolution on the Textbook Alternative Pilot approved as discussion item at the Senate. EPC Report. FSAC Report. SAC Report. CFA Report. Associated Students Report. Ex Com rep to SEC Report. 2015 Faculty Retreat preliminary discussion. Senate agenda approved.